On novel trajectory tracking control of quadrotor UAV: A finite-time guaranteed performance approach - Cao, Chengyu; Wei, Caisheng; Liao, Yuxin; Zhang, Yechen; Li, Jun (Journal of the Franklin Institute, 2022)
•A novel finite-time trajectory tracking control method for the Quadrotor UAV with consideration of external disturbances and model uncertainties is proposed.•A finite-time multivariable disturbance observer is utilized to estimate the complex lumped disturbances.•The preassigned tracking performance can be guaranteed by the newly established appointed-time prescribed performance function.•No fractional-power state or symbolic function is required in the devised controller for the finite-time convergence of the overall control system. In this work, aiming at the trajectory tracking control of the quadrotor UAV subject to external disturbances and model uncertainties, a finite-time approach with preassigned performance guaranteed is proposed. First, the control system is decoupled into translational and rotational subsystems. Then, in both two subsystems, the performance bounds constructed by the newly established appointed-time performance functions are devised for guaranteeing the tracking performance, and the controllers are designed via applying the dynamic surface control technique with integral barrier Lyapunov functions involved. Moreover, finite-time tracking differentiators and finite-time multivariable disturbance observers are exploited to estimate the target signals and the lumped disturbances, respectively. Finally, two examples of simulation are carried out to validate the effectiveness and superiority of the proposed control method.